Consumption of vitamin A rich foods and its associated factors among children aged 6–59 months in North Shoa Zone, Oromia regional state, Ethiopia - Moroda, Meseret; Goyomsa, Girma Garedew; Shukure, Rebik; Nigussu, Shelema (Frontiers in Nutrition, 2025)
BackgroundVitamin A deficiency is a major nutritional concern in poor societies, especially in lower income countries. In Ethiopia vitamin A deficiency was high in preschool children. Recently, the government of Ethiopia has been strengthening nutrition-sensitive programs that focus on promoting healthy dietary practices as a public health intervention to manage vitamin A deficiency. However, there is limited research on the consumption of vitamin A-rich foods among children aged 6–59 months in the study area.ObjectivesTo assess magnitude of consumption of vitamin A rich foods and its associated factors among children aged 6–59 months in North Shoa Zone, Oromia, Ethiopia, 2022.MethodsCommunity based cross sectional study was conducted at North Shoa Zone, Ethiopia in 2022. A total of 916 mothers’ pair children of age 6–59 months were included. A multistage stratified sampling followed by the simple random sampling technique was used to select the study participants. Data was collected through a face to face interview. STATA version 14 was used for analysis. Adjusted Odds Ratio (AOR) with a 95% CI and a P-values < 0.05 was used to declare statistical significance in the multivariable analysis.ResultsOverall, magnitude of Consumption of vitamin A rich food of children aged 6–59 months was 39.1% (95% CI: 37.71, 40.49) in a week before survey. In multivariable regression analysis, maternal educational levels above secondary education and above (AOR = 1.81, 95% CI;1.19, 2.75), paternal educational levels above secondary education and above (AOR = 1.54, 95% CI: 1.05, 2.23),house hold income 3,000 and above ET birr (AOR = 2.18, 95% CI: 1.24, 3.82),adequate dietary diversity score (AOR = 1.48, 95% CI: 1.05, 2.07),adequate meal frequency (AOR = 1.37, 95% CI: 1.04, 1.81) and had nutrition counseling (AOR = 1.31, 95% CI: 1.10, 1.73) were factors positively increases vitamin A consumption among children aged 6–59 moths, Whereas, age of children between 11 and 17 months aged 0.56 (0.33, 0.90) and 18–23 months aged 0.46 (0.29, 0.74) months was negatively associated.ConclusionThis study results showed that vitamin A consumption children aged 6–59 months was low. Strategies to increase vitamin A consumption should focus on promoting parental education, enhancing dietary diversity and meal frequency, supporting household income generation, targeting age groups in the transition to complementary feeding and strengthening nutrition counseling on child feeding practices.